Pengaruh Motivasi terhadap Kinerja Karyawan PT. PLN (Persero) Tamiang Layang - Gusti Marliani; Toto Sugiarto; Grery Varent (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2020)
This study aims to determine the effect of motivation on employee performance of PT. PLN (Persero) Tamiang Layang.The variables in this study consisted of independent variables namely Motivationor X variable and dependent variable namely Employee Performance or Y variable. The population in this study consistedof 48 peoplewith 11 people in managerialsectionand 37 people in non managerialsections. Samples were taken in non managerialsectionswith a total sampleof 30 people. Data obtainedthroughquestionnaires were analyzedandexaminedusingthe SPSS program.The resultsofthis study obtained a simpleregressionequationwiththe formula Y=36.306 + 0.036X wherethevalueof X ispositivewhichindicatesthatMotivation has a positiveeffectonEmployee Performance. Butthisisalsodeniedbyshowingthevalueoftcount = 0.200 greater>thanttable = 2.048 assumingthat H0isacceptedand Hais rejected which means that Motivationdoes not affect for employee performance.The coefficient of determination (r2) is 0.001 whichindicatesthattheindependentvariablenamelyMotivationaffectsthedependentvariableorEmployee Performance by 0.1% whiletheremaining 99.9% isinfluencedbyotherfactors not examined. Whichmeansthattheinfluenceofmotivationisonly a littleontheperformanceofemployeesof PT. PLN (Persero) Tamiang Layang.